Traditional Chinese Medicine nursing for a patient with chronic gastritis and constipation (1例慢性胃炎合并便秘患者的中医护理体会) - HOU Xuemin (侯雪敏); HUANG Yanping (黄砚萍); LI Mingzhu (李明珠) (中西医结合护理, 2023)
This paper summarized the Traditional Chinese Medicine (TCM) nursing for a patient with chronic gastritis and constipation. Based on the TCM syndrome differentiation, the Bian-stone ironing-massage and Chinese herbal medicine penetration were carried out to relieve the symptoms of constipation. The case management was adopted for regulating spleen–stomach and improving the recovery of gastrointestinal function. (本文总结1例慢性胃炎合并便秘患者的中医护理体会。通过辨证分型, 采取砭石熨摩中药透入法治疗技术, 为患者进行个案护理管理, 调理脾胃, 促进胃肠功能恢复。)